The Green Mouse - Chambers, Robert W. (Robert William), 1865-1933; Frederick, Edmund, 1870-1949 (Salt Lake City, UT : Project Gutenberg, 2003)
"The Green Mouse" by Robert W. Chambers is a novel written during the early 20th century. The story introduces a young man forced to confront his privileged yet idle life after facing financial ruin. He grapples with his lack of practical skills and contemplates a career as a magician, leveraging his unusual talents to entertain others. The narrative begins to develop his relationship with a young artist who shares a complex bond with him as they both navigate their personal struggles. At the start of the novel, readers meet a disheartened young man reeling from his family's financial collapse and his own failure to secure a stable future. Apathetic about work and life choices, he begins to consider using his talent for magic as a profession despite not being sure of its acceptance in society. This phase of his life is marked by a chance encounter with a spirited girl in Central Park, leading to a tense moment when she loses control of her horse. Their interaction ignites an immediate but complicated connection as they become intertwined in each other's lives. As the opening progresses, the groundwork is laid for both a comedic and romantic narrative, where themes of financial struggle, aspiration, and serendipity intertwine, setting the tone for their evolving relationship. (This is an automatically generated summary.)
Release date is 2003-12-01
E-text prepared by Suzanne Shell, Richard Prairie, Tonya Allen, and Project Gutenberg Distributed Proofreaders
Keywords: Fantasy fiction; New York (N.Y.) -- Fiction; Courtship -- Fiction; Magic -- Fiction